Nation, state, and the economy in history (Cambridge University Press, 2003)
At a time of persistent national strife on a world-wide scale, this book addresses the rarely-explored subject of the reciprocal relationships between nationalism, nation and state-building, and economic change. Analysis of the economic element in the building of nations and states cannot be confined to Europe, and therefore these diverse yet interlinked case-studies cover all continents. Authors come to contrasting conclusions, some regarding the economic factor as central, while others show that nation-states came into being before the constitution of a national market. The essays leave no doubt that the nation-state is an historical phenonemon and as such is liable to 'expiry' both through the process of globalisation and through the development of a 'cyber-society' which evades state control. By contrast, recent developments in southeastern Europe, the former USSR, and parts of Africa and the Far East show that building the nation-state has not run its course.